2012
DOI: 10.1085/jgp.201210838
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes during HCN channel gating defined by high affinity metal bridges

Abstract: Hyperpolarization-activated cyclic nucleotide–sensitive nonselective cation (HCN) channels are activated by membrane hyperpolarization, in contrast to the vast majority of other voltage-gated channels that are activated by depolarization. The structural basis for this unique characteristic of HCN channels is unknown. Interactions between the S4–S5 linker and post-S6/C-linker region have been implicated previously in the gating mechanism of HCN channels. We therefore introduced pairs of cysteines into these reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 41 publications
5
50
0
Order By: Relevance
“…The first two domains after the S6 segment, the C-linker and the CNBD, play a crucial role. Changes in the conformation of the CNBD, either by a cyclic nucleotide ligand (69), a short intrinsic ␤ strand of this domain (70), or mutations in residues of the C-linker and CNBD (71), result in a modulation of channel gating properties (69,70,71), and these changes in conformation of the C-linker are coupled to pore opening (69,72). Similarly, in plant Shaker channels, the first helix in the C-linker has been found to be essential for channel activity (23).…”
Section: Discussionmentioning
confidence: 99%
“…The first two domains after the S6 segment, the C-linker and the CNBD, play a crucial role. Changes in the conformation of the CNBD, either by a cyclic nucleotide ligand (69), a short intrinsic ␤ strand of this domain (70), or mutations in residues of the C-linker and CNBD (71), result in a modulation of channel gating properties (69,70,71), and these changes in conformation of the C-linker are coupled to pore opening (69,72). Similarly, in plant Shaker channels, the first helix in the C-linker has been found to be essential for channel activity (23).…”
Section: Discussionmentioning
confidence: 99%
“…In HCN channels, the A9 helix is parallel to the membrane, located just below the channel transmembrane core and in close proximity to the S4-S5 cytosolic loop, which links the fourth to the fifth transmembrane segment of the channel hydrophobic core just below the membrane. This position would allow the A9 helix to physically interact with the S4-S5 loop (Decher et al, 2004;Kwan et al, 2012). Conformational changes of the CNBD triggered by the binding of a cyclic nucleotide in HCN channels (Craven et al, 2008) or by the binding of a short endogenous b-sheet that acts as an intrinsic signal in KCNH channels (Brelidze et al, 2012) are transduced by the C-linker domain into conformational changes of channel regions present just below the membrane, displacing the A9 helix from its initial position.…”
Section: Channel Gating and The C-linker A9 Helixmentioning
confidence: 99%
“…Conformational changes of the CNBD triggered by the binding of a cyclic nucleotide in HCN channels (Craven et al, 2008) or by the binding of a short endogenous b-sheet that acts as an intrinsic signal in KCNH channels (Brelidze et al, 2012) are transduced by the C-linker domain into conformational changes of channel regions present just below the membrane, displacing the A9 helix from its initial position. Displacement of the A9 helix away from the S4-S5 loop would favor opening of the channel permeation pathway, as a consequence of the ligand-loaded status of the CNBD (Decher et al, 2004;Kwan et al, 2012). In KAT2, the A9 helix is likely to play a similar role, since replacement of the native TVRAASEFA stretch by the AtKC1 corresponding sequence AINDILRYT resulted in a mutant channel present at the PM but unable to open and mediate K + transport within the range of membrane potentials tested (+40 to 2170 mV; Fig.…”
Section: Channel Gating and The C-linker A9 Helixmentioning
confidence: 99%
“…Such displacement takes place through interactions of S4-S5 linker residues with the A 0 helix residues of the same subunit or of neighboring subunits. 27,28 Indeed, the HCN model for voltage-gating implies that S4 movements induced by membrane polarization lead to a series of conformational changes in the pore-forming module (S5-P-S6) and in the C-terminus (C-linker and CNBD domains) as well.…”
Section: Plant Shaker Channels: Similar Structure Differentmentioning
confidence: 99%
“…Moreover, it has been shown that high-affinity metal bridges made between the S4-S5 linker and the A 0 helix of a HCN channel can block the channel either in a closed state (as in the case of KAT1 or KAT2 mutants) or in an open (leak) state (as in the case of AKT2 mode 2) implying that these regions move relative to each other during gating. 28 Thus, in absence of plant Shaker crystallographic data, it is tempting to speculate that the same voltage-gating mechanism described for HCN channels could be applied to plant Shaker inwardly-and weakly-rectifying K C channels: S4 drives the C-linker relative position through the S4-S5 linker. In contrast, no functional information concerning the role of S4-S5 linker and the putative A 0 helix is available on plant outward-rectifying K C channels, but protein alignment shows that such regions significantly diverge among functional groups of plant Shaker channels and could constitute additional elements for outward rectification (Fig.…”
Section: Contribution Of the C-linker In Plant Shakermentioning
confidence: 99%